HAP2-Mediated Gamete Fusion: Lessons From the World of Unicellular Eukaryotes - Pinello, Jennifer F.; Clark, Theodore G. (Frontiers in Cell and Developmental Biology, 2022)
Most, if not all the cellular requirements for fertilization and sexual reproduction arose early in evolution and are retained in extant lineages of single-celled organisms including a number of important model organism species. In recent years, work in two such species, the green alga, Chlamydomonas reinhardtii, and the free-living ciliate, Tetrahymena thermophila, have lent important new insights into the role of HAP2/GCS1 as a catalyst for gamete fusion in organisms ranging from protists to flowering plants and insects. Here we summarize the current state of knowledge around how mating types from these algal and ciliate systems recognize, adhere and fuse to one another, current gaps in our understanding of HAP2-mediated gamete fusion, and opportunities for applying what we know in practical terms, especially for the control of protozoan parasites.